Gender disparities in the experience, effects and reporting of electronic aggression among secondary school students in Nigeria - Olumide, Adesola O (BMJ Glob Health, 2016)
BACKGROUND: Electronic aggression is the use of electronic communication technologies to harass others. It is a problem among adolescents and young people worldwide. There is a dearth of information on this problem in developing countries in spite of the increasing use of electronic media technology in these countries. OBJECTIVE: To explore gender differences in the prevalence, effects and reporting of electronic aggression among secondary school students in Oyo state, Nigeria. METHODS: A cross-sectional study was conducted using mixed methods (a quantitative survey of 653 students and 18 in-depth interviews with victims and/or perpetrators). Survey students were selected using multi-stage sampling and in-depth interviewees were selected purposively. History of electronic aggression (as a perpetrator and/or victim) in the 3 months preceding the study was obtained. Respondents also provided information on the effects of the last incident of bullying on them and whether or not they reported this incident. RESULTS: 25.8% of males and 22.1% of females had perpetrated electronic aggression, while 42.7% of females were victims compared to 36.8% of males. More females (58.1%) than males (40.3%) perpetrated electronic aggression via phone calls and more males (33.8%) than females (22.6%) perpetrated electronic aggression via chatrooms. 45.4% of male victims and 39.4% of female victims felt angry following the last cyberbully incident. Findings from the in-depth interviewees corroborated the survey findings and a male victim reported feeling very sad and even tried to stay away from school following repeated episodes of electronic aggression. More female (59.1%) than male (42.7%) victims reported the incident to someone (p=0.035). CONCLUSIONS: Incidents of electronic aggression were common and the experiences of male and female students were comparable, although more female victims reported the incidents they had experienced. Victims, especially males, should be encouraged to report incidents so that the relevant authorities can institute interventions to address the problem.